2023
DOI: 10.1111/aogs.14707
|View full text |Cite
|
Sign up to set email alerts
|

Cervix cytology samples revealed increased methylation of the human markers FAM19A4/miR1242 up to 8 years before adenocarcinoma

Ylva Lindroth,
Louise Pedersen,
Jacob Alssamaray
et al.

Abstract: IntroductionMethylation analysis of the promoter region of tumor‐suppressor genes has previously shown high sensitivity for detection of high‐grade cervical intraepithelial neoplasia (CIN) and cancer. HPV‐testing has a high sensitivity to identify women at risk to develop cancer, and has been implemented in cervical screening programs in several countries. But in most HPV‐positive women the infection will clear and they will not develop cancer. Testing for methylation could help to identify women who have pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Preliminary clinical diagnostic tests have indicated that these markers could be used for screening high-grade CIN [19,20] . Furthermore, research has shown that miR-124 is associated with the development of cervical cancer caused by HPV infection and the prognosis of HPV-induced precancerous lesions [21,22] . Therefore, further investigation is needed to understand the relationship between miR-124 and persistent HPV infection leading to cervical cancer along with its underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary clinical diagnostic tests have indicated that these markers could be used for screening high-grade CIN [19,20] . Furthermore, research has shown that miR-124 is associated with the development of cervical cancer caused by HPV infection and the prognosis of HPV-induced precancerous lesions [21,22] . Therefore, further investigation is needed to understand the relationship between miR-124 and persistent HPV infection leading to cervical cancer along with its underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%